1997
DOI: 10.1097/00005392-199709000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Ureterorenoscopic Approach to the Symptomatic Caliceal Diverticulum

Abstract: Ureterorenoscopy produces minimal morbidity and is an effective treatment of upper and middle caliceal diverticula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…[67] There are numerous disadvantages with ureteroscopic treatment including longer operative time compared to percutaneous technique and difficulty in managing lower pole CD. [67]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[67] There are numerous disadvantages with ureteroscopic treatment including longer operative time compared to percutaneous technique and difficulty in managing lower pole CD. [67]…”
Section: Discussionmentioning
confidence: 99%
“…[2] Management options for caliceal diverticular calculus include extracorporeal shock wave lithotripsy (ESWL), flexible ureteroscopy, laparoscopy, or percutaneous nephrolithotomy (PCNL). [56789] PCNL achieves high stone-free rates and in many cases causes resolution of CD. [510] In the past, staged PCNL (access by interventional radiologist followed by stone removal in the operating room) along with dilation of infundibular neck or creation of a neoinfundibulum was performed.…”
Section: Introductionmentioning
confidence: 99%
“…56 The factors influencing the success rate of retrograde interventions depend on the diverticulum position and the ureteroscope used (semirigid or flexible), and is associated with the operatory skills (being a technically demanding intervention). 57 Other recent studies reported a stone-free rate between 19-61% in cases of intrarenal stenosis associated with pyelocaliceal diverticulum treated by retrograde intrarenal surgery. 7,57,58 By comparison with SWL, retrograde intrarenal surgery as the primary technique is more efficient while also avoiding the PCNL specific morbidity.…”
Section: Pyelocaliceal Diverticulum and Calyceal Infundibular Stenosismentioning
confidence: 94%
“…57 Other recent studies reported a stone-free rate between 19-61% in cases of intrarenal stenosis associated with pyelocaliceal diverticulum treated by retrograde intrarenal surgery. 7,57,58 By comparison with SWL, retrograde intrarenal surgery as the primary technique is more efficient while also avoiding the PCNL specific morbidity. 7 Regarding the calyceal infundibular stenosis, there are few studies analyzing this subject, as it is a rather rare pathology.…”
Section: Pyelocaliceal Diverticulum and Calyceal Infundibular Stenosismentioning
confidence: 94%
“…It has been recommended to minimize high-pressure irrigation during these procedures, due to concerns that high intrarenal pressures may promote pyelovenous or pyelolymphatic migration of malignant cells. [20] However, to date, ureteroscopy and ureteroscopic resection have not been associated with a higher risk of development of metastatic disease. [21]…”
Section: Transitional Cell Carcinomamentioning
confidence: 99%